Pelaksanaan Kegiatan Mabit dalam Pembentukan Karakter Siswa di SD IT Madani Islamic School Payakumbuh - Gusti Qori Maulida; Fauzan Fauzan (Lembaga Yasin AlSys, 2026)
Character education is a systematic effort to guide, educate, and develop students’ behavior and morals so that they become accustomed to performing good deeds in accordance with the values of Islamic teachings. Character development needs to be carried out from an early age so that students have commendable behavior when entering the next stage of development. This study aims to analyze the implementation of Malam Bina Iman dan Taqwa (MABIT) activities in shaping students’ character at SD IT Madani 2 Islamic School Payakumbuh. This study used a qualitative descriptive method with a field research approach. Data were collected through direct observation, interviews with teachers, students, and parents, and documentation. The results showed that MABIT activities played a significant role in shaping students’ character, particularly discipline, independence, responsibility, and self-confidence. The implementation of MABIT activities included various spiritual and character-building activities, such as congregational prayers, religious lectures, and self-reflection. The main supporting factors for this activity were full support from the school and students’ enthusiasm, whereas limited facilities became an obstacle in its implementation. The conclusion of this study confirms that MABIT can serve as an effective strategy for Islamic character development in integrated Islamic elementary schools. The implications of this study indicate the importance of strengthening religious programs based on direct experience to support the sustainable development of students’ character.